2007
DOI: 10.1007/s00167-007-0426-5
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic ACL reconstruction with Δ plasty: an innovative approach with hamstrings’ transfer and double tibial tunnel

Abstract: We propose a new technique, with double bundle, double tibial tunnels with a bridge between them, using the hamstrings as auto-grafts, retaining either their central or peripheral attachment. A prospective series of 41 patients underwent primary reconstruction of the anterior cruciate ligament by one surgeon, arthroscopically and electronically assisted; 37 were men and 4 were women with a mean age of 24.7 years. The mean follow-up was 19.05 (12-30) months. Normal function and joint stability was achieved. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The newly improved technique of the ACL reconstruction in the study is similar to that proposed by George Papachristou [8] in 2008. In their biomechanics study, they used “Δ” plasty technique to reconstruct ACL, with two separate tibial tunnels and a femoral tunnel.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The newly improved technique of the ACL reconstruction in the study is similar to that proposed by George Papachristou [8] in 2008. In their biomechanics study, they used “Δ” plasty technique to reconstruct ACL, with two separate tibial tunnels and a femoral tunnel.…”
Section: Discussionmentioning
confidence: 63%
“…ACL reconstruction, with a success rate >90% [3] , has been the most effective way to treat ACL rupture. Surgeons refined surgical approach with many reconstructive techniques over the past years, such as the single-bundle technique, anatomic double-bundle reconstruction technique [4] , [5] , triple-bundle reconstruction technique [6] , [7] , plasty reconstruction technique [8] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with published studies of hamstring grafts. 20,21,28,41,46,47,54,57 It is difficult to show a statistically significant difference in the functional outcomes between different techniques because the results are so good with these techniques to start with. 4,30,34,49 Putnis et al 45 showed an association between a high signal intensity ratio (SIR) on MRI scans at 1 year and the graft retear rate.…”
Section: Discussionmentioning
confidence: 99%
“…40 This idea has been around since the 2000s. 4,30,41,55,57 Several different techniques have been described, but none use only the ST. 50,58 Consequently, the outcomes of the aST method are not well known. Furthermore, no study has directly compared the remodeling of aST with the standard free ST.…”
mentioning
confidence: 99%
“…26 This benefit results in proprioception improvement that allows for a more intensive rehabilitation program aimed at a faster return to sport with a performance nearing the preinjury level. 11,[27][28][29][30][31][32] This study has some limitations. Its monocentric design and the low number of patients enrolled do not allow to draw definitive conclusions about the researched topic.…”
Section: Discussionmentioning
confidence: 99%